Spatial Econometric Approach to Modelling of Selected Western Diseases - Olejnik, Alicja Anna; Żółtaszek, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
For years now, developed countries face an epidemic of high blood pressure, diabetes and high cholesterol, risk factors related to heart and circulatory disease, and a suite of psychological disorders ranging from depression, anxiety, to compulsive behaviours. These health risks have traditionally been associated with affluence, however by 2008 there is no clear link between national income and these diseases. E.g. according to Danaei, there was no relationship between national income and blood pressure in men, and in women blood pressure was even higher in poorer countries. This paper provides an in depth analysis of this correlation, applying spatial econometrics tools. The spatial aspect of the prevalence of western diseases does not seem to be obvious and, to our knowledge, is not widely explored in the literature. In particular, the paper investigates the spatial processes of selected diseases of affluence in regions of the European Union. The research covers 261 NUTS 2 regions for the period 2003–2010. This study provides the spatial analysis of circulatory and mental health disorders. In our opinion, the presented spatial econometric approach may constitute an important contribution to the field of epidemiology.